Tracing live projects in architectural education: a systematic review of experiential learning practices - Mohammed Fawzi Ragheb; Rowaida Rashed; Ayat Ismail; Mohamed Abdelkarim Salheen (Renewable Energy and Sustainable Development)
This paper discusses the growing role of live projects as experiential learning practices in architectural education. It aims to explore how live projects are conceptualized, implemented, and integrated into design curricula across diverse contexts. Employing the PRISMA 2020 framework, the study systematically reviews literature from major academic databases. Three key findings emerge: live projects enhance student learning by linking theory with practice, promote social engagement through community collaboration, and support interdisciplinary, context-responsive education. Limitations include a lack of longitudinal impact studies and inconsistencies in terminology and assessment. Drawing from the discussion and conclusion, the paper contributes a synthesized understanding of live project pedagogy, identifies operational and pedagogical challenges, and highlights their potential to reshape architectural education. It also calls for more rigorous research, sustainable institutional support, and broader adoption of live projects as a transformative model that aligns academic learning with professional and societal responsibilities. Received on, 04 April 2025 Accepted on, 27 April 2025 Published on, 08 May 2025